Healthcare bias and health inequalities towards displaced Syrians in Lebanon: a qualitative study - Riwa Khalifeh; Riwa Khalifeh; William D'Hoore; Christiane Saliba; Pascale Salameh; Pascale Salameh; Pascale Salameh; Pascale Salameh; Marie Dauvrin; Marie Dauvrin (Frontiers Media S.A., 2023)
IntroductionAccording to Lebanese official data, Lebanon hosts over 1.5 million displaced Syrians (DS). Research shows that migrants encounter barriers when accessing healthcare. The social determinants of health (SDOH) related to migration are an additional challenge for DS in Lebanon, though bias plays a significant factor in exacerbating health inequalities. This study aims to identify DS perception of healthcare biases in the Lebanese healthcare system, and its consequences on DS' accessing and receiving quality healthcare in Lebanon.MethodsA qualitative analysis using in-depth, semi-structured interviews was utilized. 28 semi-structured interviews were conducted with doctors (n = 12) and nurses (n = 16) in 2021. Six group interviews were conducted with DS (n = 22) in Lebanese healthcare facilities. The recruitment of participants relied on reasoned and targeted sampling. Thematic analysis was performed to identify common themes in participants' experiences with DS accessing Lebanese healthcare.ResultsThe findings indicated that there were barriers to accessing healthcare related to the SDOH, such as transportation and financial resources. The results also suggested that DS perceived health biases, including discriminatory behavior from Lebanese healthcare providers, stereotypes and racism leading to health inequalities.ConclusionBased on the perceptions and experiences reported by participants, the underlying causes of biases are due to the fragility of the Lebanese healthcare system when facing a humanitarian crisis as well as a collapsing infrastructure torn by past wars and the current socio-political and financial crises in the country. Global initiatives are required to provide the necessary resources needed for offering equitable health services. Such initiatives involve addressing biases, health inequities, discrimination, and the lack of a Lebanese infrastructure system for the provision of healthcare. Addressing health inequalities remains a major health objective in achieving health equity on the micro level (cultural awareness and competencies) and macro level (equitable distribution of resources, implementation of a universal health coverage) in order to guarantee quality healthcare services to DS.